2015
DOI: 10.4103/0976-0105.145778
|View full text |Cite
|
Sign up to set email alerts
|

A new venture with sclerotherapy in an oral vascular lesion

Abstract: Vascular malformations are one of the most common lesions of the oral cavity. The lesion may be a congenital malformation observed in neonates or arteriovenous malformation observed in adults. Various surgical and medical managements are possible for vascular lesions which include surgical excision, laser therapy, cryotherapy, selective embolization, intralesional sclerosing agents, β-blockers and steroid therapy. Here we report a case of oral vascular lesion where intralesional injection with 30 mg/ml of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…According to the retrospective study done by Stimpsons P, et al to treat children presenting with venous malformations of head and neck using intralesional STS, it was concluded that intralesional STS therapy offers an effective treatment option and a single treatment may be adequate for smaller lesions [14]. Complications associated with STS sclerotherapy are post-operative pain, burning sensation and infection at the site of injection, anaphylactic reaction, tissue necrosis, and sloughing [15,16]. In a more recent study Khandpur and Sharma performed sclerotherapy with 3% STS in 13 patients with venous malformation and microcystic lymphatic malformation and observed that the lesion regressed by 90-100% in 11 cases after a mean of four injections [17].…”
Section: Discussionmentioning
confidence: 96%
“…According to the retrospective study done by Stimpsons P, et al to treat children presenting with venous malformations of head and neck using intralesional STS, it was concluded that intralesional STS therapy offers an effective treatment option and a single treatment may be adequate for smaller lesions [14]. Complications associated with STS sclerotherapy are post-operative pain, burning sensation and infection at the site of injection, anaphylactic reaction, tissue necrosis, and sloughing [15,16]. In a more recent study Khandpur and Sharma performed sclerotherapy with 3% STS in 13 patients with venous malformation and microcystic lymphatic malformation and observed that the lesion regressed by 90-100% in 11 cases after a mean of four injections [17].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the procedure is simple, less invasive, and inexpensive. By using sclerotherapy, it is possible to receive treatment as an outpatient [3, 4]. However, sclerotherapy should be performed with care, because it can cause complications such as pulmonary embolism, anaphylaxis, nerve damage, increased pain, and disseminated intravascular coagulation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Craniofacial region is the most affected site (60 %) [2]. Hemangioma in oral cavity may include pain, hemorrhage, secondary infection, ulcerative lesion, and tissue transformation [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Many different sclerosing agents are used [6,7]. Among these are sodium tetradecyl sulfate (3% sterol), sodium morrhuate, sodium citrate, monoethanolamine oleate, invert sugar, boiling water and sodium phyllite [8,9,10]. This case report of a haemangioma of the right upper lip, successfully treated with an injection of absolute alcohol (98%) continued with reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%